The Processing and Interpretation of Verb Phrase Ellipsis Constructions by Children at Normal and Slowed Speech Rates. - Callahan, Sarah M.; Walenski, Matthew; Lovea, Tracy (Journal of Speech, Language & Hearing Research, 2012)
Purpose: To examine children's comprehension of verb phrase (VP) ellipsis constructions in light of their automatic, online structural processing abilities and conscious, metalinguistic reflective skill. Method: Forty-two children ages 5 through 12 years listened to VP ellipsis constructions involving the strict/sloppy ambiguity (e.g., "The janitor untangled himself from the rope and the fireman in the elementary school did too after the accident.") in which the ellipsis phrase ("did too") had 2 interpretations: (a) strict ("untangled the janitor") and (b) sloppy ("untangled the fireman"). We examined these sentences at a normal speech rate with an online cross-modal picture priming task (n = 14) and an offline sentence-picture matching task (n = 11). Both tasks were also given with slowed speech input (n = 17). Results: Children showed priming for both the strict and sloppy interpretations at a normal speech rate but only for the strict interpretation with slowed input. Offline, children displayed an adult like preference for the sloppy interpretation with normal-rate input but a divergent pattern with slowed speech. Conclusions: Our results suggest that children and adults rely on a hybrid syntax-discourse model for the online comprehension and offline interpretation of VP ellipsis constructions. This model incorporates a temporally sensitive syntactic process of VP reconstruction (disrupted with slow input) and a temporally protracted discourse effect attributed to parallelism (preserved with slow input).